PA.15 Enhanced Recovery in Elective Caesarean section: early experience suggests reduced length of stay. (9th June 2014) - Damluji, N; Maclennan, K; Jamieson, K; Tower, CL
Abstract : Introduction: Enhanced recovery (ER) after surgery is an integrated care pathway based on the principles of best peri-operative patient care.This study looked at potential benefits of introducing an ER pathway for uncomplicated elective Caesarean section (CS). Method: 52 selected women undergoing elective CS between August and November 2013 followed the pathway. Women without co-existing medical conditions were selected if uncomplicated surgery was expected. Women followed a typical ER pathway including a pre-operative drink, early catheter removal (approximately 6 hours), early feeding and mobilisation. Data was collected using a prospective audit proforma and women were telephoned the day following discharge. Results: 52 patients underwent the pathway. 32/52 (61.5%) were discharged the day following surgery, with a median length of stay of 31.25 h25 hours (range 25–120 h). 9 discharges (17%) were delayed due to neonatal reasons and 4(7.6%) due to social or domestic factors. In 7 women (13.5%) discharge was delayed due to medical reasons. Phone follow-up in 46 found 13 (28%) reported moderate pain on discharge. 3 (6%) women required re-catheterisation and 2/52 (3.8%) required re-admission (hypertension and mastitis). 95.6% of women were very satisfied or satisfied with the ER pathway. Discussion: The ER pathway is acceptable to women and can achieve discharge in the majority of women on the day following surgery, compared with 2011 when average length of stay for all CS was 5 days. Positive patient feedback and good clinical results have lead us to introduce the ER pathway as standard practise for all elective CS.